2022
DOI: 10.1039/d2nj01458k
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the boosted persulfate activation in the degradation of bisphenol A over MOF-derived cerium-doped Fe3O4 clusters with different shapes: the role of coordinatively unsaturated metal sites

Abstract: A great challenge for the application of metal-organic frameworks (MOFs) as peroxymonosulfate (PMS) activator for environmental applications in pollutant removal is stability and activity. Pyrolysis of the MOF organic linkers...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…13,14 Many studies have shown that iron-based metal-organic framework (MOF) materials with mixed-valence Fe II /Fe III have good photocatalytic activity 15 and degradation efficiency. [16][17][18] Increased Fe II content is also positively correlated with catalytic activity. 19 Chang et al 20 prepared a mixed-valence form of MIL-100 (Fe), and due to the increased ratio of Fe II /Fe III brought about by high-temperature treatment during post-treatment, the adsorption of unsaturated gas was improved.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…13,14 Many studies have shown that iron-based metal-organic framework (MOF) materials with mixed-valence Fe II /Fe III have good photocatalytic activity 15 and degradation efficiency. [16][17][18] Increased Fe II content is also positively correlated with catalytic activity. 19 Chang et al 20 prepared a mixed-valence form of MIL-100 (Fe), and due to the increased ratio of Fe II /Fe III brought about by high-temperature treatment during post-treatment, the adsorption of unsaturated gas was improved.…”
Section: Introductionmentioning
confidence: 93%
“…13,14 Many studies have shown that iron-based metal–organic framework (MOF) materials with mixed-valence Fe II /Fe III have good photocatalytic activity 15 and degradation efficiency. 16–18 Increased Fe II content is also positively correlated with catalytic activity. 19…”
Section: Introductionmentioning
confidence: 96%